Association of postmenopausal endogenous sex hormones with global methylation level of leukocyte DNA among Japanese women - Iwasaki, Motoki (BioMed Central, 2012)
BACKGROUND: Although global hypomethylation of leukocyte DNA has been associated with an increased risk of several sites of cancer, including breast cancer, determinants of global methylation level among healthy individuals remain largely unexplored. Here, we examined whether postmenopausal endogenous sex hormones were associated with the global methylation level of leukocyte DNA. METHODS: A cross-sectional study was conducted using the control group of a breast cancer case–control study in Nagano, Japan. Subjects were postmenopausal women aged 55 years or over who provided blood samples. We measured global methylation level of peripheral blood leukocyte DNA by luminometric methylation assay; estradiol, estrone, androstenedione, dehydroepiandrosterone sulfate, testosterone and free testosterone by radioimmunoassay; bioavailable estradiol by the ammonium sulfate precipitation method; and sex-hormone binding globulin by immunoradiometric assay. A linear trend of association between methylation and hormone levels was evaluated by regression coefficients in a multivariable liner regression model. A total of 185 women were included in the analyses. RESULTS: Mean global methylation level (standard deviation) was 70.3% (3.1) and range was from 60.3% to 79.2%. Global methylation level decreased 0.27% per quartile category for estradiol and 0.39% per quartile category for estrone while it increased 0.41% per quartile category for bioavailable estradiol. However, we found no statistically significant association of any sex hormone level measured in the present study with global methylation level of leukocyte DNA. CONCLUSIONS: Our findings suggest that endogenous sex hormones are not major determinants of the global methylation level of leukocyte DNA.